2017
DOI: 10.1186/s12889-017-4796-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of uptake of hepatitis B testing and healthcare access by migrant Chinese in the England: a qualitative study

Abstract: BackgroundGlobal migration from hepatitis B endemic countries poses a significant public health challenge in receiving low-prevalence countries. In the UK, Chinese migrants are a high risk group for hepatitis B. However, they are an underserved population that infrequently accesses healthcare. This study sought to increase understanding of the determinants of hepatitis B testing and healthcare access among migrants of Chinese ethnicity living in England.MethodsWe sought to obtain and integrate insights from di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 34 publications
2
47
1
7
Order By: Relevance
“…Instead, results emphasised that work- Furthermore, if patients perceive that the health care provided is not helpful to them, they are more likely to neglect opportunities to link with the self-management programme of hepatitis B. Limits to the provision of health care include lack of a subsidised healthcare system (Lee et al, 2017(Lee et al, , 2014Stanford et al, 2016), use of language that patients do not understand (Davies, Bukulatjpi, Sharma, Davis, & Johnston, 2014) and use of unsuitable media platforms for information propagation (Nguyen-Truong, Lee-Lin, & Gedaly-Duff, 2013;Zhu, Gao, Jiang, Ding, & Sun, 2015). In this study, findings indicated that the policies of chronic hepatitis B prevention largely focused on school-age students and inpatients, and that regular health check-ups for adults or labourers did not include these screenings or information.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Instead, results emphasised that work- Furthermore, if patients perceive that the health care provided is not helpful to them, they are more likely to neglect opportunities to link with the self-management programme of hepatitis B. Limits to the provision of health care include lack of a subsidised healthcare system (Lee et al, 2017(Lee et al, , 2014Stanford et al, 2016), use of language that patients do not understand (Davies, Bukulatjpi, Sharma, Davis, & Johnston, 2014) and use of unsuitable media platforms for information propagation (Nguyen-Truong, Lee-Lin, & Gedaly-Duff, 2013;Zhu, Gao, Jiang, Ding, & Sun, 2015). In this study, findings indicated that the policies of chronic hepatitis B prevention largely focused on school-age students and inpatients, and that regular health check-ups for adults or labourers did not include these screenings or information.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of patients with liver disease worldwide have suggested that patients' explanations of symptoms (such as fatigue and tiredness) may be influenced by folk health beliefs, which affect the health behaviours and management of the disease, including adopting new lifestyles or alternative/traditional treatments (Brener et al, 2016 (Fang & Stewart, 2018), remedial or healing herbs (Fang & Stewart, 2018;Giles-Vernick et al, 2016). In the patients' experience, these treatments are often used as alternative treatments instead of usual medical treatment (Fang & Stewart, 2018;Lee et al, 2017;Owiti et al, 2015). To date, conventional medical treatments for chronic hepatitis B include active adherence to antiviral medications and follow-up enhanced by developing a self-management programme (Kong et al, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 3 more Smart Citations